(3GdcJGH GdPj JJefi Cf jbQCg cd ef JMH hHYV eef dG JMHs - (3HjQj, ajdjHGs; (3GdMGaj, Sdeis ((3HjQhJs (3OGQ GdSGbjs, 2024)
(3MjGJfG JOhQ Mhd GdYdGbGJ GdYGFdI hGdCUObGA hGdRedGA hGdMHjH hMJi YdGbJfG eY faSfG dh JecfG ef JMbjb GdJhGRf ajgG JUHM MjGJfG CSgds
Keywords: (3GdYdGbGJ GdEfSGfjIs -- (3LhGfH faSjIs; (3GdYdGbGJ GdGLJeGYjIs -- (3LhGfH faSjIs; (3GdYhGWas -- (3LhGfH faSjIs; (3Yde GdfaS GdJWHjbjs